Correction: Atomic-scale detection of individual lead clusters confined in Linde Type A zeolites. Issue 5 (11th January 2023) - Fatermans, Jarmo; Romolini, Giacomo; Altantzis, Thomas; Hofkens, Johan; Roeffaers, Maarten B. J.; Bals, Sara; Van Aert, Sandra
Abstract : Correction for 'Atomic-scale detection of individual lead clusters confined in linde type A zeolites' by Jarmo Fatermans et al., Nanoscale, 2022, 14, 9323–9330, ; https://doi.org/10.1039/D2NR01819E .